Pemodelan Hidrodinamika 2-Dimensi Arus Laut Permukaan Perairan Desa Berakit Kabupaten Bintan - Nur Anisa; Mario Putra Suhana; Harish Wirayuhanto (Universitas Trunojoyo Madura, 2023)
Information related to ocean currents is not yet available in Berakit Village waters, ocean currents are an important parameter to determine the condition of a waters. An alternative that can be used to determine the condition of ocean currents is to use hydrodynamic modeling. The purpose of the study was to analyze the distribution pattern and characteristics of surface ocean currents. This research was conducted by conducting 2-dimensional hydrodynamic modeling simulating ocean currents for 1 (one) year in December 2020-November 2021 using MIKE 21 software by sampling in 6 (six) different conditions, namely at the highest tide, lowest tide, high tide. towards the ebb and flow of the full moon, the ebb towards the negligible tide, the tide towards the ebb tide and the ebb towards the negligible tide. The model results were validated by the RMSE formula with a value of 2%, the model results were very good, so that they could be used as a reference in providing an overview of the real conditions of the pattern and current distribution at the research location. The movement of ocean currents at the time of the full moon and negligible dominant currents move towards the south of the waters, while at the time of the full tide and negligible the dominant currents move towards the north of the waters. In the north season, the current velocity ranges from 0.00006 m/s-0.125 m/s with the dominant movement towards the north. East monsoon currents move predominantly north and south with speeds ranging from 0.0000003 m/s-0.129 m/s. In the south monsoon the dominant current moves to the north and south at a speed of 0.0000007 m/s-0.13 m/s. in the west season, the dominant current moves to the north and south at a speed of 0.00001 m/s-0.12 m/s. The speed of the dominant ocean currents is greater at high tide compared to low tide, this is due to differences in sea level elevation in the opposite direction of motion.Â